2011
DOI: 10.1103/physrevb.84.075332
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear transport in a small charge-tunable open quantum ring

Abstract: We experimentally study the Aharonov-Bohm-conductance oscillations under external gate voltage in a semiconductor quantum ring with a radius of 80 nm. We find that, in the linear regime, the resistance-oscillation plot in the voltage-magnetic-field plane corresponds to the quantum ring energy spectra. The chessboard pattern assembled by resistance diamonds, while loading the ring, is attributed to a short electron lifetime in the open configuration, which agrees with calculations within the single-particle mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In AharonovBohm interferometers with conserved electron current this symmetry is displayed by the "phase rigidity" of the (linear) conductance oscillations with the magnetic field B, G 1 (B) = G 1 (−B) 27,28 . Beyond linear response, the phase symmetry of the conductance is not enforced, and several experiments 29,30,[32][33][34][35][36][37] have demonstrated its breakdown. Supporting theoretical works have elucidated the role of many-body interactions in the system [38][39][40][41][42] , typically approaching the problem by calculating the screening potential within the conductor in a self-consistent manner, a procedure often limited to low-order conduction terms 38,40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…In AharonovBohm interferometers with conserved electron current this symmetry is displayed by the "phase rigidity" of the (linear) conductance oscillations with the magnetic field B, G 1 (B) = G 1 (−B) 27,28 . Beyond linear response, the phase symmetry of the conductance is not enforced, and several experiments 29,30,[32][33][34][35][36][37] have demonstrated its breakdown. Supporting theoretical works have elucidated the role of many-body interactions in the system [38][39][40][41][42] , typically approaching the problem by calculating the screening potential within the conductor in a self-consistent manner, a procedure often limited to low-order conduction terms 38,40,41 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic field symmetry of the electric conduction in the non-linear regime was addressed in several experiments : on quantum dots 14,17,37 , carbon nanotubes 38 , mesoscopic 2D metallic rings 18,[39][40][41][42] and monolayer graphene sheets 43 . Motivated by the early experiments, the first theoretical works on ballistic 15 and diffusive 16 quantum dots were completed by investigating the role of dephasing, thermal smearing, etc [28][29][30]44 .…”
Section: Introductionmentioning
confidence: 99%
“…21 However, only Keyser et al 33 have been able to show this experimentally by studying a semiconducting ring with less than ten electrons. Very recently, Hernandez et al 34 reported measurements on a 20-40electron ring but they were only able to observe the Φ 0 and Φ 0 /2 oscillations. As the effect seems to be elusive in experiments, it is necessary to study which additional factors could complicate the experimental observation of fractional periodicity.…”
Section: Introductionmentioning
confidence: 99%